The kiss - Patterson, James, 1947-; Dembowski, Jill (Patterson, James, 1947- Witch & wizard novels, 2013)
"For the first time in their lives, Wisty and Whit Allgood find themselves at odds as Wisty is drawn to a mysterious and magical stranger named Heath"--